Mobile phones and political participation in Colombia: Mobile Twitter versus mobile Facebook. Issue 2 (June 2016) - Hopke, Jill E.; Gabay, Itay; Kim, Sojung C; Rojas, Hernando
In this article, we test the relationships between Twitter and Facebook use on mobile phones and political conversation with offline and online political participation, as well as online expressive communication. Our findings show that using Twitter on mobile phones is associated with a higher likelihood for both online and offline political participation, as well as online expressive communication. Using Facebook is associated with a higher likelihood for online expressive communication only. The key contribution of this article is to show empirical differences between the relationships of social media and social networking on mobile devices with political participation and online expressive communication. Public social media apps, such as Twitter, bring mobile communication back into the public realm of a (albeit diffused) broadcast-like channel. Mobile Twitter adds to the affordances of mobility, networked connectivity, and the publicness of social media.